Efficacy and safety evaluation of cross-reactive Fibroblast activation protein scFv-based CAR-T cells - Niu, Wenhao; Wang, Binchen; Zhang, Yirui; Wang, Chaomin; Cao, Jing; Li, Jiali; He, Yong; Lei, Ping (Frontiers in Immunology, 2024)
Fibroblast activation protein (FAP) overexpression on cancer-associated fibroblasts (CAFs) is associated with poor prognosis and worse clinical outcomes. Selective ablation of pro-tumorgenic FAP+ stromal cells with CAR-T cells may be a new therapeutic strategy. However, the clinical use of FAP-CAR T cells is suggested to proceed with caution for occasional poor efficacy and induction of on-target off-tumor toxicity (OTOT), including lethal osteotoxicity and cachexia. Hence, more investigations and preclinical trials are required to optimize the FAP-CART cells and to approve their safety and efficacy. In this study, we designed second-generation CAR T cells targeting FAP with 4-1BB as a co-stimulatory molecule, and tested their cytotoxicity against FAP-positive cells (hFAP-HT1080 cells and a variety of primary CAFs) in vitro and in Cell line-derived xenograft (CDX) and a patient-derived xenograft (PDX) model. Results showed that our FAP-CAR T cells were powerfully potent in killing human and murine FAP-positive tumor cells and CAFs in multiple types of tumors in BALB/c and C57BL/6 mice and in patient-derived xenografts (PDX) model. And they were proved to be biologically safe and exhibit low-level OTOT, warranting further clinical investigation into our FAP-CAR T cells.